2022
DOI: 10.3390/nano12101644
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation of the Formation of Nickel Nanocrystallites Embedded in Amorphous Silicon Nitride Nanocomposites

Abstract: Herein, we report the mechanistic investigation of the formation of nickel (Ni) nanocrystallites during the formation of amorphous silicon nitride at a temperature as low as 400 °C, using perhydropolysilazane (PHPS) as a preformed precursor and further coordinated by nickel chloride (NiCl2); thus, forming the non-noble transition metal (TM) as a potential catalyst and the support in an one-step process. It was demonstrated that NiCl2 catalyzed dehydrocoupling reactions between Si-H and N-H bonds in PHPS to aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 50 publications
(43 reference statements)
2
17
0
Order By: Relevance
“…1(c), A09E1 shows an apparent red shift of the Si-N-Si peak. These changes in the ATR-IR spectra reveal the formation of a typical Lewis acid-base adduct via the coordination of the lone pair of =NH in ≡Si-NH-Si≡ to AlCl 3 as previously suggested for chemical modification of PHPS with cobalt (II) chloride (CoCl 2 ) [24] and NiCl 2 [25]. In addition, the peak intensity at 920 cm −1 (observed on the left shoulder of the broad peak attributed to νSi-N-Si) increases consistently with the amount of AlCl 3 used for the chemical modification of PHPS (A36E1 and A09E1 in Fig.…”
Section: Precursor Synthesissupporting
confidence: 64%
See 2 more Smart Citations
“…1(c), A09E1 shows an apparent red shift of the Si-N-Si peak. These changes in the ATR-IR spectra reveal the formation of a typical Lewis acid-base adduct via the coordination of the lone pair of =NH in ≡Si-NH-Si≡ to AlCl 3 as previously suggested for chemical modification of PHPS with cobalt (II) chloride (CoCl 2 ) [24] and NiCl 2 [25]. In addition, the peak intensity at 920 cm −1 (observed on the left shoulder of the broad peak attributed to νSi-N-Si) increases consistently with the amount of AlCl 3 used for the chemical modification of PHPS (A36E1 and A09E1 in Fig.…”
Section: Precursor Synthesissupporting
confidence: 64%
“…As suggested by the ATR-IR spectroscopic analysis, the excess AlCl 3 was coordinated with NH groups of PHPS, which could allow the Al-N bond formation via the nucleophilic attack of N of the NH groups to Al cation center of AlCl 3 followed by elimination of HCl. As another possible reaction, the released chloride anion (Cl − ) attacked other electrophiles such as the Si center of PHPS moieties to release chlorosilanes as previously discussed for chemical modification of PHPS with MCl 2 (M = Co [24], Ni [25]).…”
Section: Conversion Into Inorganic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the hydrosilylation reaction usually takes place above 120 1C in pure polysilazanes, 29 previous works showed that the presence of inorganic catalysts such as transition metals or metal complexes could remarkably lower this reaction temperature. 25,[30][31][32] However, taken separately, this can also reflect the reaction of Si-H units with TDMAT while vinyl groups polymerize.…”
Section: Synthesis and Pyrolysis Of Ti-modified Polysilazanesmentioning
confidence: 99%
“…[53] As Ni-and Co-precursors are typically reduced at temperatures beneath 400 and 500 °C, respectively, the presence of elemental metal is expected. [60,62,63] This reducibility is well reflected in the Gibbs free energy change of the different metal oxidation reactions versus the oxidation of carbon. [64] Therefore, the expected presence of metallic face-centered (fcc) Ni and Co phases could be determined by XRD measurements (Figure S12, Supporting Information) and selected area electron diffraction (SAED) (Figure S13, Supporting Information).…”
Section: Additive Manufacturing and Pyrolytic Conversion Of Metal-mod...mentioning
confidence: 99%